Pulmonary PET imaging confirms preferential lung target occupancy of an inhaled bronchodilator - Schou, Magnus; Ewing, Pär; Cselenyi, Zsolt; Fridén, Markus; Takano, Akihiro; Halldin, Christer; Farde, Lars (EJNMMI research, 2019)
Background Positron emission tomography (PET) is a non-invasive molecular imaging technique that traces the distribution of radiolabeled molecules in experimental animals and human subjects. We hypothesized that PET could be used to visualize the binding of the bronchodilator drug ipratropium to muscarinic receptors (MR) in the lungs of living non-human primates (NHP). The objectives of this study were two-fold: (i) to develop a methodology for quantitative imaging of muscarinic receptors in NHP lung and (ii) to estimate and compare ipratropium-induced MR occupancy following drug administration via intravenous injection and inhalation, respectively. Methods A series of PET measurements ( n = 18) was performed after intravenous injection of the selective muscarinic radioligand 11 C-VC-002 in NHP ( n = 5). The lungs and pituitary gland (both rich in MR) were kept in the field of view. Each PET measurement was followed by a PET measurement preceded by treatment with ipratropium (intravenous or inhaled). Results Radioligand binding was quantified using the Logan graphical analysis method providing the total volume of distribution ( V T ). Ipratropium reduced the V T in the lung and pituitary in a dose-dependent fashion. At similar plasma ipratropium concentrations, administration by inhalation produced larger reductions in V T for the lungs. The plasma-derived apparent affinity for ipratropium binding in the lung was one order of magnitude higher after inhalation ( K i ih = 1.01 nM) than after intravenous infusion ( K i iv = 10.84 nM). Conclusion Quantitative muscarinic receptor occupancy imaging by PET articulates and quantifies the therapeutic advantage of the inhaled route of delivery and provides a tool for future developments of improved inhaled drugs.